Performance Analysis and Traffic Flow Simulation of Tukad Pakerisan Road Segments Using VISSIM in South Denpasar - Tapa, I Gede Fery Surya; Yuliadewi, Ni Putu Ary; Candrawengi, Ni Luh Putu Ika; Prakasa, I Made Panji Tirta; Zainordin, Nadzirah; Sutapa, I Ketut (TIERS Information Technology Journal, 2025)
The increasing ownership of motor vehicles has significantly contributed to heightened levels of traffic congestion. This study was conducted on Tukad Pakerisan Road in Denpasar City and aims to evaluate the current performance of the road segment by employing traffic modeling through Vissim software. The research adopts the Indonesian Highway Capacity Guidelines (PKJI) as the methodological framework. Data collection was carried out via a 12-hour on-site survey across two road segments of Tukad Pakerisan. The analysis revealed that the traffic flow volume reached 2025.45 Passenger Car Station/hour on Segment A and 1865.65 Passenger Car Station/hour on Segment B. The respective road capacities were 1877.669 Passenger Car Station/hour and 1671.583 Passenger Car Station/hour. The degree of saturation was found to be 1.08 on Segment A and 1.12 on Segment B, indicating Level of Service (LOS) F—characterized by severe traffic congestion. The simulation indicates significant future congestion, with projected saturation levels exceeding 1.5, underscoring the need for integrated mitigation strategies such as adaptive signal control and vehicle restriction policies. A five-year performance projection further suggests a continual increase in the degree of saturation, surpassing the acceptable limit of 0.85 as stipulated in PKJI 2023. These findings underscore the urgent need for capacity enhancement on Tukad Pakerisan Road. The study recommends the installation of additional traffic signage and the implementation of traffic engineering strategies to mitigate congestion along this critical corridor in South Denpasar.